TV VIEWERS’ INTERPRETATION TOWARD “TRANS TV MILIK KITA BERSAMA” SLOGAN USED BY TRANS TV (A CASE STUDY ON BANJARWATI VILLAGE SOCIETY) - ISHLAHIYAH, MAZROATUL (Jurnal Ilmiah Mahasiswa FIB, 2013)
The connection between language and society can not be separated from critical discourse analysis (CDA). CDA explores the links between language use and socialpractice. It also investigates the power of language that can give influence to thesociety. The researcher conducts this study in order to know the power of Trans TVMilik Kita Bersama slogan used by Trans TV in influencing the TV viewers inBanjarwati.  However, the TV viewers are special people because they have specialcriteria such as they like Trans TV and remember Trans TV Milik Kita Bersamaslogan, and they watch TV five hours more in a day. There are three problems to besolved, namely: (1) What is the meaning of slogan Trans TV Milik Kita Bersama usedby Trans TV?; (2) How is the structure of slogan Trans TV Milik Kita Bersamaviewed from syntagmatic and paradigmatic perspectives?; (3) What is the impact ofslogan Trans TV Milik Kita Bersama used by Trans TV to the society in Banjarwativillage?. This study uses qualitative approach that applies two designs. They are contentor document analysis and case study. Document analysis is applied because the aimof this study is to describe the meaning and the structure analysis of slogan Trans TVMilik Kita Bersama. Meanwhile, case study is applied to understand the TV viewers’interpretation and the impact of slogan Trans TV Milik Kita Bersama to the society inBanjarwati by doing interview to 10 subjects (3 children, 5 adolescents, and 2 adults). This study reveals that there is the similar interpretation between the researcherand the subjects of this research about the meaning and the interpretation of sloganTrans TV Milik Kita Bersama. The subjects state that the meaning of Trans TV MilikKita Bersama is Trans TV can be owned by TV viewers covering all of level andarea. They interpret that they remember the slogan Trans TV Milik Kita Bersamabecause of the meaning and the intensity in watching Trans TV. Moreover sloganTrans TV Milik Kita Bersama is an advertisement that includes as promotional genreso they are interested and feel that they own Trans TV. However, there is differentinterpretation about the impact of slogan Trans TV Milik Kita Bersama. Theresearcher considers this slogan gives big impact to the TV viewers but they say themost powerful influence is the programs shown by Trans TV not the slogan. The researcher suggests the application of critical thinking in CDA should begiven more in time and activity thus it will be very helpful for the students to domore. Besides, the next researchers can develop and explore this topic deeper indifferent theory or object. So, it will be very useful for the knowledge developmentespecially in critical discourse analysis. Keywords: Critical Discourse Analysis (CDA), TV Viewers’ Interpretation, Trans TV Milik Kita Bersama Slogan.